Спорт жамоаларида психологик хизмат кўрсатишнинг назарий-методологик асоси (SCIENCE and SOCIETY, 2024)
In this article, the problem of providing psychological services is considered in a certain sense as one of the leading ar- eas of scientific psychology, the theoretical and methodological foundations have been studied of psychological service in sport teams.